Guest people : Hakka identity in China and abroad - Constable, Nicole; Carstens, Sharon A. (Studies on ethnic groups in China., 1996)
The essays in this volume analyze and compare what it means to be Hakka in a variety of sociocultural, political, geographical, and historical contexts including Malaysia, Hong Kong, Calcutta, Taiwan, and contemporary China.